Provenance, chemical weathering, and sedimentary environment of the aquifer sediments: Implication for arsenic enrichment in groundwater - Ming, Xiaoxing; Li, Xiaofeng; Zhang, Qiyi; Guo, Huaming; Zhang, Zhuo; Cao, Yongsheng; Shen, Jiaxing; Zhang, Chaoran (Elsevier B.V., 2024)
High arsenic (As) groundwater has been widely observed in the world, but the provenance, chemical weathering, and sedimentary environment of aquifer sediments hosting high As groundwater remain poorly understood. The geochemical and isotopic characteristics of high-resolution aquifer sediments were investigated to unravel the roles of provenance, chemical weathering, and sedimentary environment of the aquifer sediments. The average values of rare earth elements (REEs) showed the enrichment of light REEs and flat heavy REEs in the aquifer and the Yellow River sediments. The chemical index of alteration reflected incipient and moderate weathering (41 to 71). The δ13CSOM (−27.4‰ ± 4.3‰) and C/N values (8.1 ± 5.8) indicated aquatic environment of sedimentation. Shallow aquifer sediments mostly had relatively high ΣREEs contents and negative Eu anomalies, demonstrating that the aquifer sediments were mainly derived from the Yellow River (up to 94.3% ± 5%). Deep aquifer sediments had relatively low ΣREEs contents and positive Eu anomalies, which originated from the Yinshan Mountains (up to 72.2% ± 20.4%) principally with igneous and metamorphic rocks. Moreover, recycling of the Yellow River sediments from Northeastern Tibetan Plateau enhanced the silicate weathering and increased contents of Fe/Mn oxides and As. The δ13CSOM and C/N values evidenced that organisms of paleo-lake or paleo-Yellow River were responsible for abundant sedimentary organic matter. Concentrations of Fe, Mn, and As were high in shallow groundwater from the plain. The As enrichment in the shallow groundwater was jointly controlled by the provenance and chemical weathering of the aquifer sediments (14%), sedimentary environment (10%), reductive dissolution (35%) of Fe/Mn oxides, As desorption under elevated pH (20%), and competitive adsorption of HCO3- (21%). This study systematically reveals the roles of provenance, chemical weathering, and sedimentary environment of the aquifer sediments and highlights joint contributions of geochemical processes and geochemical conditions to As enrichment in groundwater.